Taxonomic notes on some Cosmarium species (Desmidiaceae, Zygnematophyceae) from Brazil - Ramos, Geraldo José Peixoto; Santos, Maria Aparecida Dos; Moura, Carlos Wallace Do Nascimento (Phytotaxa, 2021)
Taxonomic studies on desmids from the Caatinga domain, northeastern Brazil, revealed eight interesting taxa of Cosmarium: C. boeckii var. areolatum, C. clepsydra var. incrassatum, C. heptangulare, C. kanetsunae, C. pygmaeum, C. trinodulum, C. trinodulum var. brasiliense, and C. trinodulum var. pilgeri. Taxonomic notes and information on habitat are provided.